PERSEPSI MAHASISWA KEDOKTERAN TAHUN PERTAMA TERHADAP PERUBAHAN PROSES PEMBELAJARAN SKRIPSI - , RIA ROSSI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : First-year medical students who are used to teacher-centered learning in their high school education might find a new things in medical faculty which is student-centered learning. Adjustments were needed by students during transition from the teachercentered learning into student-centered learning. Adjustments of the students are considered as a factor that determines the success of learning objectives and their learning process. Objective : to investigate the perception of first-year medical students about the transition from teachercentered learning into student-centered learning. Method : A qualitative research design was conducted in this study by using document-based study. Data were collected based on reflective writings of 227 medical students using Gibbsâ reflection. Result : Students found the differences of learning method between high school and medical faculty, especially in self-study, tutorial and a lot of materials which should be learnt. Studentsâ response to the differences are varied. They found difficulties on adjustment process in early learning and still used their learning style in high school. Students have high motivation to improve their learning skills and they have plan to enhance their learning skills, especially in time management, self preparation, improving their effort, more focus and enhancing quantity and quality of their study. Conclusion : The difference between teacher-centered and student-centered, habit of studentsâ learning style in high school, and problem which is found by students in adjustment process influences studentsâ performance during learning process. Students need to improve their learning skills for a better performance during learning process.